MEDIA ARISAN: PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS AUGMENTED REALITY DENGAN ASSEMBLR EDU PADA SISWA SEKOLAH DASAR - Fauziah, Alma Amalia; Lestari, Hana; Hasanah, Tita (JURNAL KAJIAN ISLAM MODERN, 2025)
This study aims to develop Augmented Reality (AR)-based learning media called ARISAN (Augmented Reality Human Digestive System) to improve fifth-grade students' conceptual understanding of Natural Sciences (IPA) at SDN Cibatok 04. This study uses a Research and Development (RnD) model with the ADDIE approach, which includes needs analysis, design, development, implementation, and evaluation. The results of the analysis show that students' conceptual understanding is still low, especially in the digestive system material. ARISAN media is designed to provide an interactive learning experience with a 3D model of the digestive organs. Validation by experts shows that this media is very valid, with high scores from material, media, and language experts. The implementation of ARISAN media in the classroom shows a significant increase in students' conceptual understanding, with the average pretest score increasing from 48.19 to 73.52 in the posttest. The hypothesis test shows a significance value of 0.001, indicating a significant increase. Evaluations from teachers and students show that ARISAN media is interesting and easy to understand. This study concludes that AR-based learning media can improve students' conceptual understanding and provide a fun learning experience, and is expected to be a reference for the development of innovative media in the future.